2020
DOI: 10.1111/jocd.13861
|View full text |Cite
|
Sign up to set email alerts
|

Modeling lipid layers of atopic skin and observation of changes in lipid layer properties with changes in ceramide content

Abstract: Background Studies have shown that there is a high correlation between atopic dermatitis and decrease in ceramide content in the lipid bilayer of skin. Moreover, it has been shown that the reduction in ceramide content in the stratum corneum is unique to atopic dermatitis, indicating that there are particular structural differences between the lipid bilayers of normal and atopic skin. Aim This study aimed to compare the lipid bilayer of the atopic skin with that of the healthy skin and to establish a structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…10 The results of this experiment showed that three very-long-chain Cers were significantly different between groups and all of them were more abundant in women in the NS1 group. Also, by constructing lipid bilayer models of normal and atopic skin, as well as lipid bilayers containing ceramide only, Jung et al 11 found that there was a high correlation between atopic dermatitis and reduced ceramide content in the lipid bilayer of the skin, with the thickness of the lipid bilayer decreasing and it's structure weakening when the ceramide ratio was lower. This is consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…10 The results of this experiment showed that three very-long-chain Cers were significantly different between groups and all of them were more abundant in women in the NS1 group. Also, by constructing lipid bilayer models of normal and atopic skin, as well as lipid bilayers containing ceramide only, Jung et al 11 found that there was a high correlation between atopic dermatitis and reduced ceramide content in the lipid bilayer of the skin, with the thickness of the lipid bilayer decreasing and it's structure weakening when the ceramide ratio was lower. This is consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…The cornified protein envelope of keratinocytes, comprising proteins such as involucrin, loricrin, and trichohyalin, is crucial for maintaining the integrity of the physical barrier [34,35]. In the stratum corneum of patients with atopic dermatitis, levels of lipids (including ceramide), which function as a barrier, and retained water are diminished [36][37][38]. Therefore, minimizing and recovering damage to the skin barrier has been the focus of research to develop therapeutics for preventing or treating atopic dermatitis [6,11].…”
Section: Discussionmentioning
confidence: 99%
“…Aer carefully removing the water with a pipette, the uorescence spectrum was obtained with excitation at 405 nm and emission at 450-700 nm. We added 1.0 M HCl and 0.1 M NaOH to the 50 mM FDD to adjust the pH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The uorescence intensity of FDD at different H was then measured using a uorescence spectrophotometer (l ex ¼ 405 nm).…”
Section: General Procedures For Uorescence Measurementmentioning
confidence: 99%
“…3,4 Cholesterol is one of the major skin barrier lipids; about 30% of the cholesterol in the human body is synthesized in the skin, and 10% to 15% of cholesterol is metabolized through the skin. 5 A study has reported that the physiological level of cholesterol in the stratum corneum (SC) appears to exceed its miscibility with other barrier lipids, and a 0.4 : 1 : 1 M ratio of Chol/ceramides/fatty acids appears sufficient for skin lipids to limit water loss and prevent the entry of environmental substances; the stratum corneum cholesterol may have roles in the skin other than barrier function. 6 In 1974, Bouissou et al rst reported that skin and aortic walls undergo very similar morphological changes with age and atherosclerosis formation, and an increased degree of atherosclerosis is coupled with an increased skin cholesterol.…”
Section: Introductionmentioning
confidence: 99%